Fighting segregation in special needs education in the Netherlands: the effects of different funding models. Issue 4 (3rd July 2016) - Pijl, Sip Jan
ABSTRACT: In the past few decades, the number of students attending segregated special schools in the Netherlands has risen considerably. In 1975, 2.2% of all students between 4 and 11 years old attended a special school, and this percentage almost doubled to 4.3% over the next 20 years. In order to stop further growth, two new education policies came into force in 1995 and 2003: Together to School Again and the so-called Backpack . These policies differed in the way that special needs funding was allocated. Together to School Again was based on lump sum funding to schools, while Backpack was linked to the individual and based on individual needs. Neither of these policy initiatives has been particularly successful in reducing the number of students with special needs in segregated settings. In theory, lump sum funding seemed a promising option, but the combination of two different ways of funding special needs education proved to be problematic. The Dutch experience illustrates the difficulties of effecting fundamental structural changes in this field.